2009
DOI: 10.1002/pmic.200800434
|View full text |Cite
|
Sign up to set email alerts
|

The cost of resistance to colistin in Acinetobacter baumannii: a proteomic perspective

Abstract: Colistin resistance in Acinetobacter baumannii, a pathogen of clinical concern, was induced in the susceptible strain ATCC 19606 by growth under increasing pressure of the antibiotic, the only drug universally active against multi-resistant clinical strains. In 2-D difference gel electrophoresis (DIGE) experiments, 35 proteins with differences in expression between both phenotypes were identified, most of them appearing as down regulated in the colistin-resistant strain. These include outer membrane (OM) prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 101 publications
11
78
1
Order By: Relevance
“…Although they remain active against most otherwise extremely resistant A. baumannii isolates, this activity is not universal, and colistin heteroresistance has been described in A. baumannii (24), as has the development of full resistance both in vitro and in vivo (17,41). Outbreaks of polymyxin-resistant A. baumannii isolates have been reported (12,35,47). Acquired polymyxin resistance in Gram-negative bacteria is most often mediated by replacement of lipid A with aminoarabinose, which requires the products of the ugd and pbg loci and ethanolamine, mediated by pmrC.…”
Section: Colistin Resistance Is Rare Inmentioning
confidence: 99%
“…Although they remain active against most otherwise extremely resistant A. baumannii isolates, this activity is not universal, and colistin heteroresistance has been described in A. baumannii (24), as has the development of full resistance both in vitro and in vivo (17,41). Outbreaks of polymyxin-resistant A. baumannii isolates have been reported (12,35,47). Acquired polymyxin resistance in Gram-negative bacteria is most often mediated by replacement of lipid A with aminoarabinose, which requires the products of the ugd and pbg loci and ethanolamine, mediated by pmrC.…”
Section: Colistin Resistance Is Rare Inmentioning
confidence: 99%
“…Multiple studies have reported a significant fitness cost associated with colistin resistance (Fernández-Reyes et al 2009;Ló pez-Rojas et al 2011;Rolain et al 2011), leading to the hypothesis that this fitness cost may explain the lack of widespread resistance (Ló pez- Rojas et al 2011). With other antibiotics, it has been found that the cost of resistance can be overcome either by acquiring low-cost mutations or by accumulating compensatory mutations that diminish the fitness cost (Andersson and Hughes 2010).…”
mentioning
confidence: 99%
“…The laboratory-derived colistin-resistant strain ATCC 19606 ColR (MIC, 16 g/ml) possesses a single nucleotide Ala227Val mutation in pmrB (32) that is adjacent to the conserved histidine at the site of phosphorylation (His228), which is critical for phosphatase activity. The final result is the addition of phosphoethanolamine to hepta-acylated lipid A (18).…”
Section: Resultsmentioning
confidence: 99%
“…The procedures for determining chromosomal DNA fragmentation and cell wall damage in situ were first assayed for control A. baumannii strains harboring known mechanisms of colistin resistance. These were laboratory isogenic strains derived from susceptible strains from the American Type Culture Collection (ATCC; Manassas, VA), ATCC 19606 ColS (MIC, 0.25 g/ml), ATCC 19606 ColR (MIC, 16 g/ ml), ATCC 19606 ColR lpxA (MIC, 32 to 64 g/ml), and ATCC 19606 ColR lpxD (MIC, Ͼ64 g/ml) (18,32,33).…”
Section: Methodsmentioning
confidence: 99%